2002
DOI: 10.3354/cr021219
|View full text |Cite
|
Sign up to set email alerts
|

The climate of the US Southwest

Abstract: This paper summarizes the current state of knowledge of the climate of southwest USA (the 'Southwest'). Low annual precipitation, clear skies, and year-round warm climate over much of the Southwest are due in large part to a quasi-permanent subtropical high-pressure ridge over the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
404
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(416 citation statements)
references
References 95 publications
(111 reference statements)
11
404
1
Order By: Relevance
“…Precipitation variability, including recurrent drought conditions, has typified the climate of the American southwest (e.g., New Mexico, Arizona) for thousands of years (Grissino-Mayer, 1996;Sheppard et al, 2002). Dendrochronological studies and historical reports show that past droughts have caused extensive vegetation mortality across this region, best documented for the severe droughts of the 1580s, 1890s to early 1900s, 1950s, and the most recent persistent drought that began in 1996 Breshears, 1998, 2002;Swetnam and Betancourt, 1998).…”
Section: Drought-induced Dieback Of Forests and Woodlands In New Meximentioning
confidence: 99%
“…Precipitation variability, including recurrent drought conditions, has typified the climate of the American southwest (e.g., New Mexico, Arizona) for thousands of years (Grissino-Mayer, 1996;Sheppard et al, 2002). Dendrochronological studies and historical reports show that past droughts have caused extensive vegetation mortality across this region, best documented for the severe droughts of the 1580s, 1890s to early 1900s, 1950s, and the most recent persistent drought that began in 1996 Breshears, 1998, 2002;Swetnam and Betancourt, 1998).…”
Section: Drought-induced Dieback Of Forests and Woodlands In New Meximentioning
confidence: 99%
“…There have also been studies relating tree rings to the Palmer's drought severity index (PDSI), which is based on water balance calculations for a generic soil (e.g. Puckett, 1981;Meko et al, 1993;Cook et al, 2004;Leavitt, 2002;Sheppard et al, 2002;Buckley et al, 2004;Hidalgo, 2004;Zhang et al, 2004a;Taylor and Beaty, 2005). In an effort to reconstruct the 1000 year precipitation history in northeastern Qaidam Basin, Shao et al (2005) found strong correlations between tree-ring widths and a variety of climate variables, including June maximum and mean temperatures, pan evaporation rate, relative humidity, and monthly mean vapour pressure, which are all directly or indirectly related to the water balance process.…”
Section: Introductionmentioning
confidence: 99%
“…We choose to perform the numerical simulations for the winter season in Arizona, a region with dramatic contrasts in topography and local rainfall patterns [18][19][20] that provide an ideal test ground for the impact of model resolution. We choose winter because numerical models, whether global or regional, are widely known to produce substantial biases in North American summer monsoon (e.g., [21,22]), while their performance for wintertime precipitation is generally more robust.…”
Section: Introductionmentioning
confidence: 99%